Faecopneumothorax Caused by Perforated Diaphragmatic Hernia. (11th August 2020) - Necke, Kristina; Heeren, Nickolaus; Mongelli, Francesco; FitzGerald, Maurice; Fornaro, Jürgen; Minervini, Fabrizio; Metzger, Jürg; Gass, Jörn-Markus
Abstract : Incarcerated diaphragmatic hernias with intrathoracic perforation of the colon is a very rare but serious surgical emergency. A 78-year-old male patient presented to our emergency department with severe abdominal pain. A computer tomography (CT) scan revealed herniation of the left transverse colon and spleen into the thorax with colon perforation and fecal contents in the thoracic cavity. An emergent laparotomy confirmed the radiological diagnosis and showed a 6 cm dehiscence of the left diaphragm with strangulation of the left transverse colon as well as the spleen. A left-sided hemicolectomy with terminal transversostomy and splenectomy were performed. The diaphragm was closed with interrupted nonabsorbable sutures. We abstained from reinforcement of the suture line with a mesh because of the feculent contamination of the abdominal cavity. After extensive thoracoscopic lavage and insertion of two chest tubes, the patient was transferred to the intensive care unit. Diaphragmatic hernia even after a mild chest trauma can cause fatal complications. Diagnosis and treatment can be challenging and an interdisciplinary approach is recommended. Due to the associated comorbidity and long-lasting sequelae, we believe the awareness of this rare pathology as a differential diagnosis is important; both as an abdominal and thoracic emergency.